Moffat's trusts law : text and materials. - Garton, Jonathan; Probert, Rebecca; Bean, Gerard M. D. (Law in context series., 2020)
This latest edition of 'Moffat's Trusts Law' has been fully revised and updated to cover recent statutory developments and explores the impact of a wealth of new cases including the Supreme Court decisions in Pitt v. Holt (2013), FHR European Ventures v. Cedar Capital Partners (2014) and Williams v. Central Bank of Nigeria (2014). It has been restructured to incorporate a new chapter on the internationalisation of the trust which provides an understanding of the new directions being taken in the areas of trust law and equitable remedies.